Metodologia de ensaios não destrutivos com raios X para inspeção de juntas laminadas de tubulações em materiais compósitos poliméricos reforçados por fibra de vidro (PRVF) - Ferreira, Cintia Guimarães (2019)
The applications potential of X-ray image techniques using X-ray it is a subject of great interest among researchers and industry. In parallel, the use of composite materials have proportionated advances technologies in several areas. Combinations of different materials result in a component of physical, chemical and mechanical unique characteristics. The manual lamination proceeding of these polymer joints can induce defects of voids and delaminations. The objective of this work is to develop a methodology of inspection through the techniques of digital radiography, computed tomography and computerized microtomography for inspection of laminated joints of FRP. And, to analyze defect types, present in the evaluated samples, by quantifying the volumes of each phase of the material, thickness and sphericity. The results showed that the techniques detected intentionally defects inserted, in addition to others not predicted. The DR made it possible to measure the extent of defects. CT and microCT quantified volumetrically these defects, as well as the reinforcement and matrix layers. 3D images of the CT and microCT images were generated, as well planning the microCT of images.